The quality of television news in Indonesia - Vinanda Cinta Cendekia Putri; Alem Febri Sonni (ProTVF, 2022)
This research aims to explore the watching patterns of the people of Indonesia with a specific focus on how they consume news programs on television. Indonesian democracy condition is draining much information energy every year. The war for information among broadcasting institutions has stirred worry among the general public regarding the quality of the content broadcast by national television stations. Virtually no medium is safe from the touch of politics, and news programs, in particular, are often highly political. Due to the urgency of this research to measure the quality of programs, not the number of viewers, the informants of this study are industry experts and academics. Their knowledge, experience, and insight into the television industry make them exceptionally qualified to assess television programs' quality critically. The results of the evaluation and deepening of the experts can be concluded by several aspects of the quality of news programs: The intervention of media owners is still evident and even conspicuous in the balance of news in an industry where broadcasting institutions are explicitly manipulating news content, especially when it concerns political issues. Concerning critical power, several news programs fail to arouse a critical rationale. News is delivered from one perspective only. The supervision aspect is still deficient because the shocking and horrible are intrinsically appealing. Subjectiveness in the news is widespread, especially in the selection of titles and narratives that simply justify the reporters' words.